Economics of uniqueness in Croatian historic towns looking for new urban models - Urošević, Nataša; Grubišić, Danijela (2020)
The paper will elaborate on the current situation and development perspectives in selected Croatian historic towns, reflecting upon innovative models of urban regeneration and social revitalization. Looking for new urban models in the challenging global context, the authors applied the concept of cultural economy or the economics of uniqueness, which connects sustainable urban development with strategic mobilisation of unique local cultural resources. As a case study, the current situation in the cities of Pula and Šibenik (Croatia) was elaborated, which are characterized by the transition from former military and industrial urban models to cultural tourism destinations.
U radu je prikazana trenutna situacija i perspektive razvoja u odabranim hrvatskim povijesnim gradovima, promišljajući o inovativnim modelima urbane obnove i društvene revitalizacije. U potrazi za novim urbanim modelima u izazovnom globalnom kontekstu, autori su primijenili koncept kulturne ekonomije ili ekonomije jedinstvenosti, koja povezuje održivi urbani razvoj sa strateškom mobilizacijom jedinstvenih lokalnih kulturnih resursa. Kao studija slučaja prikazana je trenutna situacija u gradovima Puli i Šibeniku (Hrvatska), koje karakterizira prijelaz s nekadašnjih vojnih i industrijskih urbanih modela na odredišta kulturnog turizma.
Bibliografija: 35 jed.
Summary ; Sažetak.
Keywords: Kulturni turizam -- Povijesni gradovi -- Održivi razvoj; Šibenik -- Pula -- Hrvatska